2018
DOI: 10.1159/000487585
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Dacryoliths from Patients with or without Topical Rebamipide Treatment

Abstract: Background : A dacryolith mainly contains organic material, but its specific protein content is unknown. We observed a unique dacryolith formation in patients with long-term use of rebamipide eye drops and tried to identify the differences in protein compositions of dacryoliths from patients with or without use of rebamipide eye drops using novel proteomic analysis. Methods: Dacryolith samples were obtained from 7 patients (4 samples were without rebamipide usage, 3 were with rebamipide usage) who underwent en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The first proteomic analysis of MPC-Ds (dacryoliths) in the context of rebamipide treatment was conducted in 2018 as well, identifying the proteins present in MPC-Ds [37]. Here, we link these findings to the localization of various antigens in the tissue, employing IF.…”
Section: Discussionmentioning
confidence: 99%
“…The first proteomic analysis of MPC-Ds (dacryoliths) in the context of rebamipide treatment was conducted in 2018 as well, identifying the proteins present in MPC-Ds [37]. Here, we link these findings to the localization of various antigens in the tissue, employing IF.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectroscopic analysis of dacryoliths has revealed the presence of several proteins, including hemoglobin, albumin, lysozyme, S-100A8, S-100A9, cathepsin, neutrophil elastase (NE), neutrophil gelatinase-associated lipocalin, myeloperoxidase, lactotransferrin, and prolactin-inducible protein showing that most core proteins of dacryoliths are involved in immune and inflammatory responses. 21 These findings, when taken with electron microscopic features, provide new insights into the possible etiopathogenesis of dacryolith formation.…”
Section: Etiopathogenesis Of Dacryolithsmentioning
confidence: 90%
“…1,7,9–11 This review aims to elucidate and reconstruct the possible sequence of events in the etiopathogenesis of noninfectious dacryolithiasis, drawing primarily on basic science work carried out over the last decade by the authors’ group, but also by other groups. 5–30…”
mentioning
confidence: 99%
“…The content of dacryoliths was found to be organic material with minerals such as calcium and magnesium 14 . In addition, Mano et al reported that the protein pro les of dacryoliths were different between ROS and non-ROS group 15 . However, the exact composition of organic material is unclear in either with or without ROS application.…”
Section: Chemical Analysis Of Lacrimal Concretionsmentioning
confidence: 99%